The Implementation of Collaborative Governance in The Literacy Education Empowerment Program Within Indigenous Communities in Lebak Regency - Indriani, Nisa; Sumardjo; Sarma, Ma'mun (Sodality: Jurnal Sosiologi Pedesaan, 2024)
This study examines the implementation of collaborative governance in literacy education empowerment programs within indigenous communities. The collaborative governance approach involves the central government, local government, institutions, and the community. The aim of this research is to describe the collaborative governance in the literacy education empowerment program within indigenous communities and analyze the factors affecting community participation and empowerment. Data was collected through a census, with a sample of 200 learners from three literacy education assistance-receiving institutions in the Indigenous Community. The approach used includes descriptive analysis and data analysis with Structural Equation Modeling (SEM). The research results indicate that collaborative governance has been established. Significant factors influencing the level of participation in this program are the level of collaboration, environmental support, optimization elements, and the characteristics of the community members. Factors significantly influencing the level of empowerment are the level of collaboration, environmental support, participation, and the characteristics of the community members, while optimization elements do not significantly affect empowerment. The research findings suggest that the program is running fairly well, although there are some challenges such as the availability of infrastructure, the lack of training for tutors, and funding sources solely from the central government budget.